Comparison of physician practice patterns for older adults compared to NHANES diabetes cohort on oral/other therapy. (February 2013) - Shaya, Fadia T; Chirikov, Viktor V; Bron, Morgan; Howard, DeLeonardo; Foster, Clyde; Yan, Xia; Khanna, Niharika; Warrington, Verlyn O
The American Diabetes Association and European Association for the Study of Diabetes issued a new patient-centered approach for the management of hyperglycemia in patients with Type 2 diabetes. With a focus on older adults and the elderly, the authors explored the alignment of elements of the suggested framework with patients' reports of receiving combination or monotherapy using US national survey data (National Health and Nutrition Examination Survey 2001–2010) and a physician survey. Combination therapy was positively associated with age (range: 1.56–1.63; p = 0.04–0.07), obesity (odds ratio [OR]: 1.40; p = 0.01), HbA1c ≥7.0 (OR: 2.00; p < 0.01), number of years of living with diabetes (OR: 1.02 per year; p = 0.01) and hyperlipidemia (OR: 1.36; p = 0.02). An interaction term between years of living with diabetes and comorbidities >1 pointed to a trend of those with comorbidities >1 to be less probable to report combination therapy (OR: 0.98; p = 0.07) per additional year of diabetes history. Results suggest that sicker, older patients might benefit from more aggressive therapy, in the context of diabetes prevalence, this is expected to continue rising in that population.